Modern neurosurgical techniques to remove intraorbital foreign bodies – report of two cases - Napora, Katarzyna; Obuchowska, Iwona; Łysoń, Tomasz; Sieśkiewicz, Andrzej; Bień, Maciej; Mariak, Zofia; Mariak, Zenon (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
To indicate the usefulness of modern neurosurgical techniques to remove intraorbital foreign bodies, not removed during primary ophthalmological surgical intervention. Patient 1: A 29-year-old man, struck with a bottle, with a piece of glass located at the top of the right orbit. During the primary ophthalmological intervention – orbitotomy accessed through the conjunctiva of the fornix of the upper eyelid and the second cut through the wound in the eyelid – the foreign body was not removed. The patient was moved to the Department of Neurosurgery, where 3 days after the injury the 30 mm x 7 mm piece of glass was successfully removed with the aid of neuronavigation system. The surgical approach was through a cut in the right eyebrow and the foreign body was found to be located in the back-top part of the orbit. Patient 2: A 30-year-old man, hit with a piece of wood, with an organic foreign body (wood), located in the mid-lower and medial part of the right orbit. During the primary ophthalmological operation – orbitotomy accessed through the conjunctiva of the fornix of the lower eyelid – the foreign body was not removed. The patient was moved to the Department of Neurosurgery, where the surgeon unsuccesfuly attempted to remove the foreign body through the wound in the conjunctiva of the fornix of the lower eyelid with the aid of neuronavigation. In this situation the endoscopic technique with access through the nose was used. The mid part of the medial orbit wall was removed and partially fragmented piece of wood was located with the use of the neuronavigation. The foreign body was located in the middle part of the orbit, near the medial wall. It was removed in four pieces measuring: 8 mm x 3 mm, 8 mm x 4 mm, 15 mm x 5 mm, 18 mm x 6 mm.